2021
DOI: 10.3390/ma14164614
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rigid Segment Type on Copoly(ether-ester) Properties

Abstract: The growing ecological awareness of society created the tendency to replace petrochemically based materials with alternative energy carriers and renewable raw materials. One of the most requested groups of polymer materials with significant technological importance is thermoplastic elastomers (TPE). They combine the properties of elastomers such as flexibility with the typical properties of thermoplastics, like easy processing. Herein, one compares the influence of rigid segments on the properties of copoly(es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
(54 reference statements)
1
6
0
Order By: Relevance
“…It has been reported that the C–O bond is weaker than C–C bond, resulting in lower stress at break under deformation in PPDL . The polar nature of the functional groups, molar mass, and degrees of crystallinity can also affect the materials’ strength. These multiple competing effects may have influenced the ultimate strength of the materials, and further investigations are necessary to comprehensively understand this behavior.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the C–O bond is weaker than C–C bond, resulting in lower stress at break under deformation in PPDL . The polar nature of the functional groups, molar mass, and degrees of crystallinity can also affect the materials’ strength. These multiple competing effects may have influenced the ultimate strength of the materials, and further investigations are necessary to comprehensively understand this behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The copolymers with higher flexible segment content do not display yield point, due to the initiation of highly elastic deformations at low deformation, which was also observed in the authors' previous works. 62 The Young's modulus decreases significantly, and PHF-b-F-pTHF2000 25/75 has around 46 times the lower value of the Young's modulus compared to PHF. Furthermore, the stress at the break value of PHF-b-F-pTHF2000 25/75 is about 14 MPa lower than the stress at the break value of PHF-b-F-pTHF2000 75/25.…”
Section: Mechanical Propertiesmentioning
confidence: 96%
“…Thermoplastic elastomers (TPEs) are a class of materials that combine the mechanical properties of elastomers and the processing properties of thermoplastics. [ 11 ] This is because of their morphology, which can be divided into rigid and flexible segments. Compared to traditional elastomers, the rigid TPE segment forms physical crosslinking instead of chemical crosslinking.…”
Section: Introductionmentioning
confidence: 99%